A new ectoparasitic Aulacothrips (Thysanoptera: Heterothripidae) from Amazon rainforest and the significance of variation in antennal sensoria - Cavalleri, Adriano; Kaminski, Lucas A.; Mendonça Jr., Milton S. (Zootaxa, 2012)
Aulacothrips amazonicus sp.n. is described from Northern Brazil, with larvae and adults ectoparasitic on ant-tended Membracidae (Hemiptera) on Solanum shrubs. This new taxon differs from its congeners by (i) body distinctively paler; (ii) sensoria on antennal segments III & IV much less convoluted; (iii) male tergite IX posterior margin straight and with several long and stout setae. The possible biological significance of interspecific differences in antennal sensoria among Aulacothrips species is discussed.